Pengelolaan Arsip Dinamis - Wardah, Mutiawatul (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2016)
Archives have a very important role in many aspects of life. Beside as an information source, an archive is also an authentic evidence that can be accounted for righteousness. Therefore, the authors of this paper focus on